Stress-Induced Microspore Embryogenesis Requires Endogenous Auxin Synthesis and Polar Transport in Barley - Pérez-Pérez, Yolanda; El-Tantawy, Ahmed-Abdalla; Solís, María Teresa; Risueño, María C.; Testillano, Pilar S. (Frontiers in Plant Science, 2019)
Stress-induced microspore embryogenesis is a model in vitro system of cell reprogramming, totipotency acquisition and embryo development. After induction, responsive microspores abandon their developmental program to follow an embryogenic pathway, leading to in vitro embryo formation. This process is widely used to produce doubled-haploid lines, essential players to create new materials in modern breeding programs, particularly in cereals, although its efficiency is still low in many crop species, since the regulating mechanisms are still elusive. Stress signaling and endogenous hormones, mainly auxin, have been proposed as determinant factors of microspore embryogenesis induction in some eudicot species; however much less information is available in monocot plants. In this study, we have analyzed the dynamics and possible role of endogenous auxin during stress-induced microspore embryogenesis in the monocot Hordeum vulgare, barley. The results showed auxin accumulation in early proembryo cells, from embryogenesis initiation and a further increase with embryo development and differentiation, correlating with the induction and expression pattern of the auxin biosynthesis gene HvTAR2-like. Pharmacological treatments with kynurenine, inhibitor of auxin biosynthesis, and α-(p-chlorophenoxy)-isobutiric acid (PCIB), auxin antagonist, impaired embryogenesis initiation and development, indicating that de novo auxin synthesis and its activity were required for the process. Efflux carrier gene HvPIN1-like was also induced with embryogenesis initiation and progression; auxin transport inhibition by N-1-naphthylphthalamidic acid (NPA) significantly reduced embryo development at early and advanced stages. The results indicate activation of auxin biosynthesis with microspore embryogenesis initiation and progression, in parallel with the activation of polar auxin transport (PAT), and reveal a central role of auxin in the process in a monocot species. The findings give new insights into the complex regulation of stress-induced microspore embryogenesis, particularly in monocot plants for which information is still scarce, and suggest that manipulation of endogenous auxin content could be a target to improve in vitro embryo production.